Change Management in Business Processes - Maryam yarmohammadi; Ali Moeini; Kambiz Badie (Journal of Information Technology Management, 2012)
Today, change is a definite phenomenon and organizations should make themselves aligned with requirements for survival and success in the competitive market and retain customers. One of the main components of any organization that is undergoing these changes is the business processes of that organization. In other words, in a dynamic business environment, business processes are changed at runtime. What is important is the ability to make changes in the process correctly and verify the process before using it. One of the possible solutions is using an executable model with the process model. In order to provide a solution, in this paper we present a framework for applying the changes and verify them via integration of UML2.0 activity diagram as a standard technique for business processes modeling and colored Petri net as an executable model.